CUSTOMER DECISION MAKING IN SELECTING FUTSAL COURT IN MANADO IN TERMS OF PERCEIVED QUALITY: AS APPLICATION OF ANALYTICAL HIERARCHY PROCESS (AHP) - Tumbelaka, Andro; Kindangen, Paulus; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2015)
Sports is a necessity for everyone and become a lifestyle in society. No exception for this sport type, Futsal. In order to keep existing customers and for attracting new ones, every futsal court needs to identify the criteria on which customers determine their futsal selection decision. Therefore the writer conducted to analyze the criteria of Futsal court that influence customer and analyze the most preferred futsal court by customer in Manado. Writer used Analytical Hierarchy Process (AHP) to compare each futsal court as the alternative. The sample of this research is the customers of My Futzal, Champion Futsal, and Marina Futsal as many as 40 respondents of purposive sampling. As the result, there are top three criteria that have the highest influence on customer in selecting futsal court in Manado. Access to the stadium gets the highest score. Second highest score goes to aesthetics and cleanliness of facilities, and then parking criteria in third place. Therefore, every futsal courts particularly in Manado has to pay attention toward these three factors in order to maintain and attract customers. My Futzal is the most preferred Futsal court by the customer. Followed by Champion Futsal and then Marina Futsal. Keywords: customer decision making, perceived quality, futsal selection.